Editorial: maybe our 'Barrett's recommendation speech' should change?. Issue 9 (3rd April 2017) - Richter, J. E.
Abstract : Linked Content This article is linked to Erichsen et al paper. To view this article visithttps://doi.org/10.1111/apt.13962 .